The impact of covid-19 pandemic on syphilis notifications in northeast Brazil - Silva, Wictor Hugo de Souza; Santos, Marcos Daniel Seabra; Seabra, Mônica Santos de Melo; Oliveira, Makson Gleydson Brito de (Revista JRG de Estudos Acadêmicos, 2024)
This study aims to evaluate the impact of the COVID-19 pandemic on the number of syphilis notifications (acquired, during pregnancy and congenital) in northeastern Brazil. An ecological study was carried out using the database provided by the Ministry of Health through the Department of Informatics of the SUS (DATASUS). The monthly numbers of notifications of acquired, gestational and congenital syphilis were organized on the Google Sheets online platform and the data were statistically analyzed, using the Wilcoxon test, for the pandemic (Jan/2020-Jun/2021) and pre pandemic periods (Jan/2018-Dec/2019), with a statistical significance of 5%. There was a reduction in the number of notifications of total cases of syphilis in the Northeast in 2020 and in 2021 when compared to the pre-pandemic period (p < 0.001 and p = 0.031, respectively). This reduction represents a drop of 32.38% in 2020 and 28.84% in 2021. Regarding the states, there was no statistical significance in the number of notifications for Sergipe in 2020 (p = 0.638), Ceará in 2021 (p = 0.156) and Rio Grande do Norte in 2021 (p = 0.219) compared to 2018 and 2019. In addition, it was observed that in Sergipe there was an increase of 53.96% in notifications in 2021 compared to the same period (p = 0.031). These variations may be a consequence of social distancing, the reallocation of resources during the pandemic and socioeconomic issues, or even all of these factors combined.